Perioperative anesthesia care for the pediatric patient undergoing a kidney transplantation: An educational review. Issue 11 (20th August 2021) - Voet, Marieke; Cornelissen, Elisabeth A. M.; van der Jagt, Michel F. P.; Lemson, Joris; Malagon, Ignacio
Abstract: Living‐donor kidney transplantation is the first choice therapy for children with end‐stage renal disease and shows good long‐term outcome. Etiology of renal failure, co‐morbidities, and hemodynamic effects, due to donor‐recipient size mismatch, differs significantly from those in adult patients. Despite the complexities related to both patient and surgery, there is a lack of evidence‐based anesthesia guidelines for pediatric kidney transplantation. This educational review summarizes the pathophysiological changes to consider and suggests recommendations for perioperative anesthesia care, based on recent research papers.